Characterization Of Thermostable And Alkalitolerant Cellulase From Endophytic Fungus Bartalinia Sp - Yadav, Rajnish (My University, 2013)
Endophytic fungi are untapped reservoir and not much has been exploited for industrially important enzymes. In this study an endophytic fungus Bartalinia sp. isolated from leaf litter, Western Ghats, India was used for studying the cellulase enzyme production and its characterization. It has been considered that some endophytic fungi have evolved a biochemical system for the degradation of cellulosic substrates and the basis of this study is that some endophytic can change their lifestyle to saprobes. This may be correlated to the enzymes that fungi produce. Bartalinia sp. was screened for cellulase and effect of pH, temperature along with carbon and nitrogen sources on cellulase activity were evaluated from the crude extract. Also agricultural wastes like wheat straw, rice straw, eucalyptus leaves, bamboo leaves, rice bran, bagasse were used for evaluating their effect on cellulase activity. Furthermore, pH change and biomass produced was monitered and zymographic analysis was also done. The result obtained indicated that cellulase activity was affected by the change in temperature, pH along with carbon and nitrogen sources. Optimum activity of CMCase obtained at 100° C was startling and enzyme is stable both at acidic and alkaline pH. From the study it was revealed that cellulase produced by Bartalinia sp. was thermostable and alkali-tolerant.
MS, DBTES
Keywords: Bartalinia sp,Endophytic fungi